2022
DOI: 10.3389/fonc.2022.988287
|View full text |Cite
|
Sign up to set email alerts
|

Derivation, validation and assessment of a novel nomogram-based risk assessment model for venous thromboembolism in hospitalized patients with lung cancer: A retrospective case control study

Abstract: PurposeThis study aimed to develop and validate a specific risk-stratification nomogram model for the prediction of venous thromboembolism(VTE) in hospitalized patients with lung cancer using readily obtainable demographic, clinical and therapeutic characteristics, thus guiding the individualized decision-making on thromboprophylaxis on the basis of VTE risk levels.MethodsWe performed a retrospective case–control study among newly diagnosed lung cancer patients hospitalized between January 2016 and December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…For example, D‐D, a specific fragment resulting from the degradation of cross‐linked fibrin, is used as sensitive biomarker of endogenous fibrinolysis and hypercoagulability status. It has been established by several studies that D‐D level was an independent risk predictor of VTE in various types of cancer, 17,27–30 and these results are highly in line with those from our study ( β 95% CI: 1.000–1.002, p = 0.009).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, D‐D, a specific fragment resulting from the degradation of cross‐linked fibrin, is used as sensitive biomarker of endogenous fibrinolysis and hypercoagulability status. It has been established by several studies that D‐D level was an independent risk predictor of VTE in various types of cancer, 17,27–30 and these results are highly in line with those from our study ( β 95% CI: 1.000–1.002, p = 0.009).…”
Section: Discussionsupporting
confidence: 93%
“…Our current data suggested the forecast accuracy of the ROC curve for nomogram model (AUC = 0.981, 95% CI: 0.964-0.998, p < 0.001) was significantly higher than those of other models, concerning the comparison of the current model with other existing models. 17,[27][28][29][30] However, some limitations of this investigation should not be ignored. First, relatively small sample size, single-center for screening resulted in selection bias to a certain extent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Beside those factors, previous studies [ 22 , 23 ] mainly focused on the postoperative VTE risk in lung cancer. A recently reported study [ 27 ] established a nomogram-based risk assessment model for venous thromboembolism, but the number of enrolled patients was relatively limited. Compared with previous models, our study developed a nomogram model based on a large number of patients with a more general representation for lung cancer VTE risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…According to remarkable evidence from systematic review as well as cohort and case-control studies, obesity is an independent factor for VTE and might predispose to thromboembolic events. 10 , 31 33 With respect to BMI, it was shown that the majority of participants had a baseline BMI within the normal range according to WHO cut-off points (18.5-24.9 kg/m 2 ) and only 10.26% of the patients were obese with BMI values over 30 kg/m 2 . Nevertheless, 18.76% of patients were classified as obese according to the Chinese population standards.…”
Section: Discussionmentioning
confidence: 99%